KÁSIPLIK PÁNLERDI OQITIWDA DIDAKTIKALIQ PRINCIPLERDIŃ ÓZINE TÁN TÁREPLERI - Amanbaev, M.; Kurmanov, A. (SCIENCE and SOCIETY, 2022)
The article examines the specificity of didactic principles by informing students about the achievements of science and technology, the services of scientists, engineers and workers.